Uncertainty during chance and its impacts on jop satisfaction, psychological well-being, organizational commitment and effects of communication - Karakuş, Filiz (My University, 2005)
Araştırmanın amacı, örgütsel değişimin sebep olduğu belirsizliğin psikolojik sağlık, iş tatmini ve örgütsel bağlılık üzerindeki negatif etkilerini bulmaktır. Aynı zamanda, araştırmada, değişim sürecinde etkin iletişimin psikolojik sağlık, iş tatmini ve örgütsel bağlılık üzerinde pozitif etkisinin varolup olmadığı da incelenmiştir. Model, Türkiye’de değişim sürecinde bulunan özel bir bankada çalışan 100 kişi üzerinde test edilmiştir. Örgütsel değişim sonucu ortaya çıkan belirsizliğin, psikolojik sağlık, iş tatmini ve örgütsel bağlılık üzerinde negatif etkisi olduğu bulunmuştur. Aynı zamanda, etkin iletişimin, değişim süreci boyunca, psikolojik sağlık, iş tatmini ve örgütsel bağlılık üzerinde pozitif etkisi olduğu bulunmuştur. Araştırmada, belirsizlik, faktör analizi sonucunda stratejik-yapısal belirsizlik ve görevsel belirsizlik olarak ikiye ayrılmıştır. Değişkenler arasındaki ilişkiyi detaylı bir şekilde incelemek amacıyla yaptığımız regresyon analizinde stratejik-yapısal belirsizliğin psikolojik sağlık ve iş tatmini üzerinde olumsuz etkisi olmadığı görülmüştür. Öte yandan, görevsel belirsizlik ile örgütsel bağlılık faktörleri- duygusal, süreklilik ve normatif arasında anlamlı bir ilişki de bulunmamıştır.

The aim of the study was to investigate the negative effects of organizational uncertainty caused by organizational change on psychological well-being, job satisfaction and organizational commitment. On the other hand, we also tried to find out whether the effective communication has a positive effect on psychological well-being, job satisfaction and organizational commitment or not, during the change. The model was tested with a sample of 100 employees from one of the leading private banks in Turkey which is in the period of change. Uncertainty caused by organizational change was found to be negatively related with job satisfaction, organizational commitment and psychological well-being. At the same time, effective communication was found to have positive effects on the psychological well-being, organizational commitment and job satisfaction at the times of uncertainty. In this study, uncertainty yielded into two factors after the principal component analysis as strategic-structural uncertainty and task related uncertainty and it was seen that there is no significant relationship between strategic-structural uncertainty and psychological well-being and job satisfaction. Moreover, no significant relationship between task related uncertainty and components of organizational commitment –affective, normative and continuance commitment was seen.
Keywords: Örgütsel Davranış_Psikoloji; Örgütsel Değişim_İş Tatmini